A host factor supports retrotransposition of the TRE5-A population in Dictyostelium cells by suppressing an Argonaute protein. Issue 1 (December 2015) - Schmith, Anika; Spaller, Thomas; Gaube, Friedemann; Fransson, Åsa; Boesler, Benjamin; Ojha, Sandeep; Nellen, Wolfgang; Hammann, Christian; Söderbom, Fredrik; Winckler, Thomas
Abstract Background In the compact and haploid genome ofDictyostelium discoideum control of transposon activity is of particular importance to maintain viability. The non-long terminal repeat retrotransposon TRE5-A amplifies continuously inD. discoideum cells even though it produces considerable amounts of minus-strand (antisense) RNA in the presence of an active RNA interference machinery. Removal of the host-encoded C-module-binding factor (CbfA) fromD. discoideum cells resulted in a more than 90 % reduction of both plus- and minus-strand RNA of TRE5-A and a strong decrease of the retrotransposition activity of the cellular TRE5-A population. Transcriptome analysis revealed an approximately 230-fold overexpression of the gene coding for the Argonaute-like protein AgnC in a CbfA-depleted mutant. Results TheD. discoideum genome contains orthologs of RNA-dependent RNA polymerases, Dicer-like proteins, and Argonaute proteins that are supposed to represent RNA interference pathways. We analyzed available mutants in these genes for altered expression of TRE5-A. We found that the retrotransposon was overexpressed in mutants lacking the Argonaute proteins AgnC and AgnE. Because theagnC gene is barely expressed in wild-type cells, probably due to repression by CbfA, we employed a new method of promoter-swapping to overexpressagnC in a CbfA-independent manner. In these strains we established an in vivo retrotransposition assay that determines the retrotransposition frequency of the cellular TRE5-A population. We observed that both the TRE5-A steady-state RNA level and retrotransposition rate dropped to less than 10 % of wild-type in theagnC overexpressor strains. Conclusions The data suggest that TRE5-A amplification is controlled by a distinct pathway of theDictyostelium RNA interference machinery that does not require RNA-dependent RNA polymerases but involves AgnC. This control is at least partially overcome by the activity of CbfA, a factor derived from the retrotransposon's host. This unusual regulation of mobile element activity most likely had a profound effect on genome evolution inD. discoideum .